Implementation of the Project Based Learning (PjBL) Method in Enhancing Student Creativity - Maisyarah (Global Action and Education for Society, 2025)
The use of conventional teaching methods remains a common challengen in educational institutions, as these methods often appear monotonous, leading to a decline in student’s interest in learning. This situation inhibits learner engagement and prevents the from developing creativity or achieving maximum result. This study aims to analyze the application of the Project Based Learning (PjBL) method at UPT SD Negeri 388 Gresik and the challenges it faces. This study employs a qualitative approach, gathering data through observations, interviews, and document anaysis. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The result showed that the application of the Project Based Learning (PjBL) method consisted of six statges, namely starting with fundamental questions, designing project, developing schedules, monitoring students and project progress, testing result, and evaluating experiences. However, in its implementation this method faces obstacles because not all students have the same interests, tend to prefer to play, and are difficult to direct.